Impact of Credit Rating Changes on the Malaysian Stock Market - Abdul Rashid, Hafidz Rizal (2010)
This thesis examines the reaction of common stock returns to bond rating changes for the period 2002 - 2010 in Malaysia. Many of the findings are consistent with previous research in other markets. Downgrades are found to produce significant negative reaction prior to the rating announcement and after the announcement. Upgrades on the other hand produce no significant results. Further analysis on firm size with regard to downgrades found small firms produce more pronounced negative returns than large firms. However the analyses on the price impact according to rating agency and rating changes to below investment grade category are inconclusive. Overall, the results offer mixed evidence on the information content of bond rating changes and by implication, the state of market efficiency in Malaysia. Nevertheless, the results have to be treated with caution as the regression outcome during the estimation of abnormal returns violated the assumptions of homoscedasticity and normality of residuals, which make the results less suitable for making inferences.